Chemometric Analysis on Fingerprints of Acalypha Indica L Based on the Different Drying Methods - Hayati, Elok Kamilah; Anggraini, Maulinda Putri (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
The use of an anting-anting plant (Acalypha indica Linn) as a raw material of herbal medicine requires a standardized process in its production. This research aims to determine the fingerprint pattern of active compounds using a thin-layer chromatography method with specific samples that applied various drying methods, such as direct sunlight drying, greenhouse drying, and oven drying at 50°C. The chemometrics data interpretation with the Principal Component Analysis (PCA) method was applied to analyze the obtained fingerprint patterns to identify the differences among the variations. The separation of active compounds in the anting-anting plant using ultrasonic extraction for 20 minutes with ethyl acetate as the solvent. Consecutively, the thin-layer chromatography fingerprint was investigated by applying a subsequent comparison of mobile phase cyclohexane: toluene: diethylamine by 75:15:10. The result from the TLC plate spots was examined to detect the differences among the fingerprints, with the help of ImageJ and Orange software. The fingerprints with various drying methods resulted in the possession of 11 stains of active compounds. The ImageJ software generated chromatograms with Area Under the Curve (AUC) values, further subjected to chemometrics analysis using PCA. The PCA results showed simple grouping patterns for each variation, with a total principal component (PC) of 86.03% (PC1 = 52.78%, PC2 = 33.25%), indicating the success criteria of PCA chemometrics analysis.